Prevalence of Extensively Drug Resistant Salmonella typhi and its Susceptibility against Meropenem, Tigecycline, Fosfomycin and Azithromycin among Clinical Isolates from a Tertiary Care Hospital Laboratory : Susceptibility in Extensively Drug Resistant Salmonella typhi - Irfan, Zona; Afridi, Faisal Iqbal; Fatima, Ambreen; Zafar, Hira; Muhammad Pervaiz, Yousra; Farooq, Lubna (Pakistan Journal of Health Sciences, 2024)
The emergence of Extensively Drug-Resistant (XDR) Salmonella typhi in Pakistan has posed a significant public health challenge. Traditional antibiotics, including ampicillin, chloramphenicol, and fluoroquinolones, have become ineffective due to widespread resistance, necessitating the exploration of alternative treatment options. Objective: To assess the in vitro efficacy of four antibiotics fosfomycin, tigecycline, meropenem and azithromycin against XDR Salmonella typhi strains isolated from patients in Karachi, Pakistan. Methods: A cross-sectional study was conducted at the Department of Microbiology, Ziauddin University Hospital, Karachi, over six months. Blood samples from both inpatients and outpatients aged 1 to 60 years were collected for culture and sensitivity testing. Antibiotic susceptibility was determined using the standard disc diffusion method. Data were analyzed to evaluate the effectiveness of the selected antibiotics against XDR Salmonella typhi. Results: The susceptibility patterns of Salmonella typhi and XDR Salmonella typhi revealed that meropenem, azithromycin, tigecycline, and fosfomycin were effective in all tested samples. Conversely, antibiotics such as ampicillin, aztreonam, cefixime, ceftriaxone, chloramphenicol, co-trimoxazole, and ciprofloxacin demonstrated resistance, with varying patterns observed between Salmonella typhi and XDR Salmonella typhi. The distribution of XDR and Non-XDR Salmonella typhi cases by gender and age, with no significant association found between these variables and XDR status. Conclusions: Meropenem and azithromycin remain effective against XDR Salmonella typhi; however, fosfomycin and tigecycline present promising alternatives. These findings underscore the need for continuous surveillance and the development of new treatment strategies to combat the rising threat of XDR Salmonella typhi in Pakistan.